PENGARUH LAYANAN INFORMASI TERHADAP PERENCANAAN PEMILIHAN KARIR SISWA KELAS IX MTs DARUL HIKMAH PEKANBARU - Safrudin Safrudin; Tri Umari; Sardi Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research was conducted as motivated by 1). In most anxious students inchoosing a career, 2). Most student do not get information about careers, 3). Most of the studentaffected their friends in the choice of carrer, 4). The majority of students opposed to the opinionof parents in career choice. The purpose of this study is 1). T reveal the student’s career planningbefore given information services, 2). To reveal the student’s career plans after giveninformation services, 3). To find the difference before and after given information services to thestudent of class IX MTs Darul Hikmah Pekanbaru in their career planning, 4). To determine theinfluence of information services to the students career planning class IX MTs Darul HikmahPekanbaru. In this study that will be examined is the student to 1). Self understanding, 2).Planning a future, 3). Knowledge of workplace information, 4). Attitudes of decision-making. Inthis study, researchers used an method with quasi experimental technicues. Data clectin toolssuch as questionnaires statement. The populatin of this study are students of class IX MTs DarulHikmah Pekanbaru 2013/2014 as many as 61 students. Which consists 0f 33 students clss IX.Aand IX.B. analysis f the data using statistical techniques with the percentage formua, todistinguish students palinning careers elections before and after the given information servicesused test “t”. from the results of the test “t” obtained tcal obtained tstandard at the level of 5%(16.445>1.980). Thus Ho is rejected and Ha accepted. Which mean that in this study there aredifferences regarding the slection of students career planning before and after given informationservices. Then from the calculation of the product moment r= 0.80 coefficient determinant can beseen that there is a 64% contribution to the planning of information services for career chicestudents class IX of MTs Darul Hikmah PekanbaruKey words: Choice of career planning, MTs Darul Hikmah Pekanbaru, Information service.